Pengaruh Pendidikan dan Pelatihan, Kompensasi terhadap Kinerja Petugas Aviation Security (AvSec) Melalui Motivasi Kerja di Bandara Sultan Thaha Jambi - Erdiansyah, Nove; Syekh, Saiyid; Yamali, Fakhrul Rozi (Universitas Batanghari Jambi, 2024)
This research aims to analyze the influence of education and training, compensation on the performance of Aviation Security (AvSec) officers through work motivation at Sultan Thaha Jambi Airport. The method used in this research is descriptive verification and quantitative methods, with a sample size of 46 people. This research uses the PLS analysis method. The research results show that 1) education and training variables have a positive and significant effect on work motivation, but compensation variables do not have a significant effect on work motivation; 2) education and training variables, compensation variables and work motivation variables have a positive and significant effect on performance; and 3) education and training variables have a positive and significant effect on performance through work motivation, but compensation variables do not have a significant effect on performance through work motivation for aviation security (AvSec) officers at Sultan Thaha Jambi Airport.